Síntese de materiais compósitos micro-mesoporosos visando a captura de CO2 - Silva, Silvia Caroline Gomes dos Santos (2015)
factor responsible for climate change worldwide. In recent years, several research are intended to developing new methods and technologies to capture and separation CO2. The use of the adsorption method for separating CO2 is a promising alternative in view of the potential to reduce energy costs by eliminating aqueous solutions and providing capture and regeneration rates adequate. In this context, this paper presents the synthesis of composite type materials ZSM-12 / MCM-41 and ZSM-12 / MCM-48, seeking to combining the properties of the zeolitic material to the structural advantages of mesoporous materials, resulting in obtaining materials with high CO2 adsorption capacity. For this, the materials were synthesized by hydrothermal method and mechanosynthesis. The materials were characterized by XRD, absorption spectroscopy in the infrared, thermal analysis, adsorption-desorption analysis of N2 A 77 K, SEM and TEM. The CO2 adsorption capacity of these materials were investigated by gravimetric analysis. The results obtained from the characterization techniques showed that the synthesis methodology, used for desilication phase of ZSM-12, was efficient in obtaining a composite material with integrated micro and mesoporous phases. On the other hand, the results showed that by mechanosynthesis was possible to obtain materials formed by mixing between the micro and mesoporous phases. Also, comparing the results of adsorption CO2 the obtained composite materials by hydrothermal method with those obtained by mechanosynthesis it was concluded that the adsorption capacity is influenced by crystallinity and amount of the phase ZSM-12. The results showed from adsorption, in general, ZM48-75 samples, ZM41 A/MH R3 and ZM41-50 showed higher adsorption capacity than pure zeolitic and mesoporous materials, respectively. Thus, the composite materials of the type ZSM-12/ZSM-41 and MCM-12/MCM-48 are promising adsorbents for CO2 separation.